Computational problems of FE-analysis of elastic-plastic surface structures - Bielski, J.; Radwańska, M. (Computer Assisted Methods in Engineering and Science, 2001)
The paper contains a review of problems connected with numerical analysis of elastic-plastic surface structures. Given is detailed information about finite elements as well as about the algorithm of physically non-linear analysis using the incremental-iterative Newton- Raphson method with the consistent modular matrix. The main goal of the paper is to compare numerical results obtained with elements based on either the volume or area approach to the formulation of physical relations. The presented examples are obtained with the use of computer code MANKA. They illustrate some numerical problems induced by elastic-plastic deformation of chosen types of plates.